Reading the Old Testament in the 21st century using the Book of Jonah as reference - Spangenberg, Izak J. J. (Verbum et ecclesia, 2013)
Some Old Testament scholars identify three main types of approaches to the Bible, namely, (1) theological (2) historical and (3) literary. Others would rather refer to different methods of studying the Bible, which can be linked to different worlds. Some methods focus more on the world behind the text, others on the world of the text itself, whilst yet a third group focuses more on the world in front of the text. One reads the text according to which of the three worlds one regards as the most important. Although there is truth in all of these classifications of approaches to studying the Bible and methods of doing so, the audience for whom the reading is done plays an even more important role. The different audiences often cherish different views of Scripture which can be linked to a specific paradigm and which dominates the outcome of the reading process. The fact is illustrated by investigating how the book of Jonah has been read and studied in recent years.